Penyalahgunaan dadah dan kewajaran peruntukan hukuman berat ke atas penagih dan pengedar dadah di Malaysia: satu analisis - Mohd. Noor, Azman (University of Malaya, 2010)
Drug is the country’s no one enemy. Drug abuse has caused a lot of social problems, crimes and wasted many of youth’s lives who are supposed to be the futere asset to the country. The goverment has spent a lot of money to set up rehabilitation centres, provide facilties and means of rehabilitative treatement for the drug addicts. This paper will investigate Islamic rulings for drug abuse and drug trafficking and the justifications for imposing capital punishment for the drug trafficker.